Чисельно-польовий аналіз потужності магнітних втрат в трифазному індукторі магнітного поля - Мілих, Володимир Іванович; Шилкова, Лариса Василівна (НТУ "ХПІ", 2019)
Представлено принципи і результати чисельно-польового розрахунку потужності магнітних втрат (ПМВ) в індукторі магнітного поля, подібному до статора асинхронного двигуна. Метод розрахунку заснований на пошуку максимумів значень магнітної індукції в безлічі міні-секторів, на які ділиться один період структури зубців і ярма осердя статора, що повторюється. За розподілом знайдених максимумів визначаються їх середньоквадратичні значення на вказаних ділянках осердя, і по них обчислюється ПМВ. Метод дозволяє відображати розрахункові моделі осердь практично будь-якої форми. Проведено порівняльний аналіз ПМВ в режимі неробочого ходу для варіантів осердя статора за відсутності і з одним рядом аксіальних вентиляційних каналів. Порівняльні розрахунки зроблені на прикладі конкретного індуктора при різних кількості і діаметрах каналів.

The principles and results of the numerical-field calculation of the magnetic loss power (MLP) in a magnetic field inductor similar to an asynchronous motor stator are presented. The calculation method is based on the search for the maxima of the magnetic induction values in a multitude of minisectors into which one period of the repeating geometric structure of the teeth and the stator core yoke are divided. The maximum for each minisector is selected by its analogues in all periods of this structure. According to the distribution of the maxima found, their rms value is determined fora specified period of the core areas. And the MLP is already calculated by the rms value. The method allowsto display the calculation models of cores of any shape and practically doesn't require the simplification of their geometric structure. Comparative analysis of the MLP in idle mode for variants of the stator core in the presence and absence of axial ventilation ducts is carried out. Using the example of a specific inductor with one row of circular ducts, comparative calculations are made for their different numbers and diameters. The presented method is the basis for targeted variation of almost any ducts structure when choosing the optimal variant in terms of MLP level and inductor cooling conditions.
The numeral-field analysis of power of magnetic losses is in the three-phase inductor of magnetic-field
Keywords: статор асинхронного двигуна; осердя; вентиляційні канали; магнітна індукція; порівняльний аналіз; magnetic field inductor; asynchronous motor stator; core